9/11 as False Flag: Why International Law Must Dare to Care. Issue 3 (August 2017) - Benjamin, Amy Baker
Abstract : At the heart of contemporary international law lies a paradox: the attacks on the United States of September 11, 2001 have justified 16 years of international war, yet the official international community, embodied principally in the United Nations, has failed to question or even scrutinise the US government's account of those attacks. Despite the emergence of an impressive and serious body of literature that impugns the official account and even suggests that 9/11 may have been a classic (if unprecedentedly monstrous) false-flag attack, international statesmen, following the lead of scholars, have been reluctant to wade into what appears to be a very real controversy. African nations are no strangers to the concept of the false flag tactic, and to its use historically in the pursuit of illegitimate geopolitical aims and interests. This article draws on recent African history in this regard, as well as on deeper twentieth-century European and American history, to lay a foundation for entertaining the possibility of 9/11-as-false-flag. This article then argues that the United Nations should seek to fulfil its core and incontrovertible 'jury' function of determining the existence of inter-state aggression in order to exercise a long-overdue oversight of the official 9/11 narrative.